Chiral Amplification during Asymmetric‐Induced Copolymerization of Phenylacetylenes with Tight Cis‐Cisoidal Main Chains. Issue 14 (27th May 2013) - Liu, Lijia; Mottate, Kazuomi; Zhang, Geng; Aoki, Toshiki; Kaneko, Takashi; Teraguchi, Masahiro
Abstract A novel phenylacetylene (1) having two hydroxyl groups and a chiral pinanyl group together with the other three related phenylacetylenes has been synthesized and (co)polymerized by using an achiral catalytic system. Among the four monomers, only 1 is suitable to the asymmetric‐induced polymerization (AIP). Chiral amplification phenomenon is only observed in the copolymerization of 1 with an achiral phenylacetylene having two hydroxyl groups (3). The tight helical cis‐cisoidal main chain formed by making intramolecular hydrogen bonds between the hydroxyl groups in the copoly(1/3) enhances the efficiency of chiral induction and as a result chiral amplification phenomenon is observed during the copolymerization.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>